Sejarah Harmonisasi Hukum Adat Dan Hukum Negara Dalam Masyarakat Rejang - Riqqah D Ramadhanty; Nopan Wiranata; Ismail Munir; Alimni Alimni (UIN Fatmawati Sukarno Bengkulu, 2023)
This study aims to explain the history of harmonization of Customary Law, Islamic law, and state law in the Rejang community by using the socio-legal method, namely an approach that collaborates legal research approaches with non-legal approaches, namely social sciences, anthropology, and history. The results of the study show that harmonization between customary law, Islamic law and constitutional law is urgently needed as an effort to fulfill the rights and needs of every citizen, including indigenous peoples, and to create solutions to customary problems that cannot be resolved by national law. In the Rejang community, harmonization between customary law, Islamic law, and state law is manifested in a customary law forum called Jenang Kutei. The Jenang Kutei trial has become a space for the Rejang people to realize their customary law values based on Islamic religious law, which has received support from the local government in the form of legal recognition in the form of regional regulations. The results of the research show that the existence of Jenang Kutei in the Rejang community can create harmonization between customary law, Islamic law, and state law